War and revolution in the origins of the Oriental State of Uruguay, 1810-1830 - Frega, Ana (History and Culture, 2023)
This article broadly presents the revolution of independence in a border territory between Spain and Portugal: the oriental band of the Uruguay River. It focuses on the ideas of José Artigas, radical expression of the revolution in the Río de la Plata for his early proposals for independence from Spain, his recognition of the sovereignty of the peoples and their rights to form a political unit on an equal footing, and the defense of the “most miserable”. Some aspects of the revolution are outlined below from the perspective of Afrodescendants and indigenous populations. Finally, the article examines the military defeat of Artiguismo and the realization of independence, with British mediation, which led to the formation of the Oriental State of Uruguay.
Keywords: Río de la Plata Revolution; José Artigas; Oriental Province; Oriental State of Uruguay; Patriot army; Socio-ethnic conflicts; Afro descendants; Independence; Sovereignty